Peran Sarana Pembelajaran dalam Mendukung Kemampuan Keterampilan Siswa SMK Program Keahlian Teknik Pemesinan Serang - Sulaeman Deni Ramdani; Ismi Maulani; Moh Fawaid (Department of Mechanical Engineering Education, 2019)
This study aims to analyze the role of learning facilities in supporting the skills of vocational students in Machining Departments in Serang. The method used in this study is a quantitative descriptive method. The population is 49 students of class XI majoring in machining. Data were collected using a questionnaire and were analyzed using the quantitative-descriptive technique. The examined variables are the workplace (bench work, metal measurement & testing, turning work, milling work, grinding work) with four aspects of learning facilities (furniture, equipment, educational media, other equipment), and skills (imitation, manipulation, precision, articulation, naturalization. The study finds that aspects of learning facilities are in the